Progress in the photodynamic therapy treatment of Leishmaniasis - Vital-Fujii,D.G. (2021)
Leishmaniasis is a serious and endemic infectious disease that has been reported in more than 90 countries and territories. The classical treatment presents a series of problems ranging from difficulty in administration, development of resistance, and a series of side effects. Photodynamic therapy (PDT) has already shown great potential for use as a treatment for leishmaniasis that is effective and non-invasive, with very minor side effects. PDT can also be inexpensive and easy to administer. In this review, we will report the most recent developments in the field, starting with the chemical diversity of photosensitizers, highlighting important mechanistic aspects, and noting information that may assist in designing and developing new and promising photosensitizer molecules.